2016
DOI: 10.1177/2168479015604182
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis Between the Top-Selling Drugs in the Japanese Pharmaceutical Market and Those in the United States, the United Kingdom, France, and Germany

Abstract: These results suggest that the Japanese market will rival overseas markets in the near future. Pharmaceutical companies should seriously consider operating within Japan, whose market is currently transitioning to a global market.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Our results demonstrated that the mainstream of the current drug development focusing on anticancer drugs and especially on molecular targeted drugs, 25,26 and the highest ratio of molecular targeted agents in prescription pattern of drugs was observed in treatment of hematologic malignancies in Japan. 27,28 The findings of the present study suggested that medical costs for cancer as well as other diseases have continuously increased, although the pace of the increase may decline if precision medicine or related regulations are properly introduced.…”
Section: Discussionmentioning
confidence: 70%
“…Our results demonstrated that the mainstream of the current drug development focusing on anticancer drugs and especially on molecular targeted drugs, 25,26 and the highest ratio of molecular targeted agents in prescription pattern of drugs was observed in treatment of hematologic malignancies in Japan. 27,28 The findings of the present study suggested that medical costs for cancer as well as other diseases have continuously increased, although the pace of the increase may decline if precision medicine or related regulations are properly introduced.…”
Section: Discussionmentioning
confidence: 70%
“…6 Focusing in on the anticancer pharmaceutical market in Japan, there are indeed a lot of unmet medical needs, especially in oncology; with the indirect encouragement of the research and development of anticancer therapy by the Japan government, this area may be one of the most promising therapeutic areas in the near future. [7][8][9][10] In this context, drug development in Japan can be initiated with an eye on the global market, aiming for near-simultaneous regulatory approval for OVT products worldwide. 1 Of course, sufficient preclinical/clinical data must be collected to initiate drug development.…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Japan reportedly accounted for approximately 10% of global sales, which was the second largest share in the world. 1,2 Various differences have been reported between the current Japanese pharmaceutical market and markets of Western countries. The share of cardiovascular system drugs is relatively high among the top 100 drugs in the Japanese market, while that of antineoplastic and immunomodulating agents is relatively low.…”
Section: Introductionmentioning
confidence: 99%